Moderating effect of social capital on community empowerment and economic well-being - Sarjiyanto Sarjiyanto (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
Improving community economic well-being based on community empowerment plays an important role in rural development. This study aims to determine the ability of social enterprises in Indonesia (Village-Owned Enterprises/BUMDes) to improve the community's economic well-being through empowerment programs and the role of social capital in rural community development. At social conditions at the basic level, very little attention is paid to the development of deprived communities. Starting from the experience of rural community economic empowerment programs through the establishment of Village-Owned Enterprises (BUMDes) in Indonesia, this study will test three hypotheses: (1) whether there is an effect between community empowerment and the economic well-being of rural communities; (2) is there an effect between social capital and the economic well-being of rural communities; and (3) is the effect between community empowerment and economic well-being mediated by social capital? Multiple regression analysis is used to examine the effect between community empowerment and community economic well-being. This analysis highlights the central role of social capital in mediating the effect between community empowerment and economic well-being. Community empowerment is significantly related to social capital. These effects between social capital, community empowerment, and economic well-being apply to theories and measures of rural community empowerment.